Decreased circulating mtDNA levels in professional male volleyball players - Nasi, M.; Cristani, A.; Pinti, M.; Lamberti, I.; Gibellini, L.; De Biasi, S.; Guazzaloca, A.; Trenti, T.; Cossarizza, A. (International Journal of Sports Physiology and Performance, 2016)
Purpose: